Pengaruh Lingkungan Sekolah terhadap Hasil Belajar Siswa MA - Ikrom, Bonafid; Darmawan, Didit (Malewa: Journal of Multidisciplinary Educational Research, 2024)
The researcher aims to see how the school environment affects learning outcomes in Madrasah Aliyah (MA) students. The school environment, which includes educational facilities, interactions between students and teachers, and learning atmosphere, is believed to have an important role in improving students' academic achievement. This study examines various related scientific sources. The results of this study indicate that a good school environment, including good facilities, teacher support, and positive social interactions, significantly contribute to improving students' academic achievement. A supportive environment can tend to achieve good academic achievement in students compared to those in less conducive environments. This study emphasizes the importance of attention to the development of the school environment to support student success.